A Spectral-Difference Scheme for Three-Dimensional Vorticity Equations with Single Periodical Boundary Condition (Journal of Computational Mathematics, 1991)
We develop a spectral-difference scheme to solve three-dimensional vorticity equation with single periodical boundary condition. We prove the conservation, generalized stability and convergence. The numerical experiments show that this scheme gives much better results than usual difference schemes.